THE STUDENTS’ PERCEPTION TOWARD IMPLEMENTING BLENDED LEARNING METHOD IN ENGLISH LANGUAGE TEACHING (ELT) AT THE 5th SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT - Talis, Sri Sherli Novianti; Akib, Erwin; Baso, Farisha Andi (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2018)
The objective of this research to find out the students’ perception toward implementing Blended learning method in English Language Teaching (ELT) at fifth semester students English Department Makassar Muhammadiyah University. This research applied the descriptive method for the data collection by using the close-ended questionnaire consisting 15 statements, open-ended questionnaire consisting 5 numbers, and 5 numbers for lecturer interview. The data was taken from 35 students in a class by using purposive sampling technique. The result of this research was of this study gave their positive perception toward the implementing BL method in ELT. The positive judgment from the respondents came from their experience in learning by received BL method. It can be seen from the students' questionnaire, their agreement was showed that they enjoy in learning when the lecturer implementing BL method. Besides that, the benefit of BL method for the students made them more interested in learning. It is also can be seen from students’ questionnaire that they got some benefits from the method, one of them was the students become more active and responsible for learning.